Hasil Analisa Beberapa Unsur Kimia Dalam Makanan Indonesia (Lanjutan) - Grecia Maharani (Jurnal Kimia dan Kemasan, 1978)
In addition of the study "Trace element in Indonesia foodstuff", chlorinated hydrocarbon pestisides and poly chlorinated biphenyls (PCB) were determined . All productra were low in total D.D.T., lindane, and PCB.